The Influence of Child, Households, and Villages/Sub-Districts Characteristics on The Working Status of Children in East Nusa Tenggara Province 2024 - Prayoga, Angga; ., Budiasih (Politeknik Statistika STIS, 2025)
The percentage of the poor population in East Nusa Tenggara Province is being thefourth highest in Indonesia in 2024, but the highest percentage of child labor in Indonesia. Thepurpose of this study is to find out the picture, influencing factors, and trends of factors affectingchild labor in East Nusa Tenggara Province in 2024. The unit of analysis was children aged 10-17 years who were unmarried and not as head of household with a sample of 9,117 children from6,123 households and 1,165 villages/sub-districts. The data used are Susenas Kor and ModulesMarch, as well as Podes 2024 sourced from BPS. The analysis method in this study is multilevelbinary logistics regression. The results of the study show that children who work are boys aged15-17 years. The child lives in households with a low level of head of households’ education andhousehold work in the agricultural sector, a small number member of productive age, and havemicro and small enterprises, and live in villages/sub-districts with many micro and smallindustries and the main source of income for most of the population in the agricultural sector.